2019
DOI: 10.1155/2019/8150793
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Survey of Trace Heavy Elements in Insecticides

Abstract: There are many types of insecticides traded in the local and international markets, which vary depending on the type of target insect (e.g., whether crawling or flying). This paper aimed to assess the concentration of trace elements present in the various pesticide formulations (solid, liquid, and gaseous). This study was conducted in two groups: the first group was comprised of zinc, copper, iron, chromium, phosphorus, selenium, and cobalt; the second group included four heavy toxic elements (arsenic, thalliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Uranium, Mn, Br, As, La, Se, Hg, Cr, Rb, Fe, Zn, Co, Eu, Sb and Ni elements were found in trace levels in the four types of liquid pesticides. The analysis results comparison of element contents in liquid pesticides were not significantly different from the research conducted by Alnuwaiser [3], as shown in Table 3. The amounts of toxic heavy metals detected in liquid pesticides were less than in solid pesticides.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Uranium, Mn, Br, As, La, Se, Hg, Cr, Rb, Fe, Zn, Co, Eu, Sb and Ni elements were found in trace levels in the four types of liquid pesticides. The analysis results comparison of element contents in liquid pesticides were not significantly different from the research conducted by Alnuwaiser [3], as shown in Table 3. The amounts of toxic heavy metals detected in liquid pesticides were less than in solid pesticides.…”
Section: Resultsmentioning
confidence: 55%
“…Pesticides are substances specifically designed to control, prevent, or fend off insects, rodents, nematodes, weeds, viruses, bacteria, and micro-organisms that are considered as pests found in animals and humans [2]. The use of pesticides by farmers aims to control the plant pests in order to increase the crop yields, but pesticides may cause environmental pollution if they are used incorrectly [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A chemical analysis of several pesticides, including 11 glyphosate-based herbicide formulations, by utilizing inductively coupled plasma/optical emission spectrometry (ICP-OES) detected As, Cr, Co, Pb, and Ni as contaminants [38]. A similar analysis of several insecticides using ICP mass spectrometry detected Zn, Cu, Cr, Co, Pb, and Tl (thallium) as contaminants [39]. It has been suggested that the HM elements contaminate pesticide products during the manufacturing process, while some of them are intentionally added as nano pesticides for increased efficacy [38,40].…”
Section: Pesticide Applicationmentioning
confidence: 99%
“…The contamination of agricultural soil with heavy metals is a global environmental issue. This problem is primarily caused by the excessive and unregulated use of agrochemicals [ 1 , 2 ] such as phosphate fertilizers, fungicides, herbicides, and insecticides that contain heavy metal impurities including As, Cd, Co, Cu, Hg, Ni, Pb, and Zn [ 3 , 4 ]. Application of organic fertilizers such as livestock manure and compost has been reported as source of heavy metals in agricultural soils.…”
Section: Introductionmentioning
confidence: 99%